Preventive Military Strike: From American Patriotism to the Threats of International Security - V. P. Kirilenko; G. V. Alekseev (Управленческое консультирование)
Review for a monograph Farkhutdinov I. Z. “American Doctrine of Preventive Military Strike from Monroe to Trump: International Legal Aspects”. M. : EURASNIIPP, 2017. 338 p.The monograph of the prominent Russian expert in the field of international law, Insur Zabirovich Farkhutdinov “The American Doctrine of Military Strike from Monroe to Trump: International Legal Aspects” sparked a lively scientific discussion around the problem of the use of force in the modern international system. On the one hand, to preserve the global legal order, it is absolutely necessary to intervene internationally in the political situation where human rights are violated, on the other hand, the unjustified use of force creates the threat of escalating political instability and undermines international security. It seems reasonable to conclude that the Monroe Doctrine was created as a political instrument to protect the US from interference by foreign governments in the internal affairs of America, but became a means of spreading national sovereignty to spaces with an international regime and the territory of other countries.